A numerical method approach for analyzing the effects of joint orientation on stability of open-stope in metalliferous mines - Verma R.; Jaiswal A.; Avchar A. (My University, 2025)
This research is focused on evaluating the effects of joint orientation on the stability of open stopes. Joints are often seen as the source of failure in an open stope. Joint orientation adversely affects the stability of the open stope by majorly causing non-uniformity in stress and providing a surface for free movement of strata. Effect of joint orientation on stope stability is less discussed with few publications. This study exclusively identifies the effect of joint orientations on stope stability with the help of numerical model designed in finite difference method computer software. In this research, different rock strengths were considered to determine how joint orientations ranging from 0 to 165 degrees affect the stability of open stopes having variable horizontal to vertical stress ratio values and thus the failure behavior is obtained. The application of the results of this research in the metal mining industry should lead to improved understanding of the effects of joint orientation on stope stability for different rock strata at variable depths, and hence useful in devising a suitable design method of mining metal orebody that offers optimum stope span, maximum production and required factor of safety. © 2019 Lavoisier. All rights reserved.